2010
DOI: 10.1063/1.3299023
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Jahn–Teller splitting with O 1s x-ray absorption spectroscopy in strained Nd1−xCaxMnO3 thin films

Abstract: Electronic structures of strained Nd 1−x Ca x MnO 3 ͑NCMO͒ thin films with x = 0 to 0.8 are investigated via x-ray absorption spectroscopy ͑XAS͒. The obtained O 1s spectra within the photon energy 529-535 eV can be decomposed into e g ↑ 1 , e g ↑ 2 , t 2g ↓, and e g ↓ bands. Based on the assigned energy levels of these band states, the energies of magnetic exchange, crystal field and Jahn-Teller ͑JT͒ splitting are determined. Particularly, the JT splitting is around 0.8 eV, which is observed with O 1s XAS for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The oxygen K‐edge XANES spectra (Figure c) display a peak at 531 eV, which is assigned to the transition from O 1s to O 2p/Co 3d . De Groot et al, reported that the peak at 531 eV is related to the metal 3d states, which might be split into two peaks assignable to t 2g and e g .…”
Section: Resultsmentioning
confidence: 95%
“…The oxygen K‐edge XANES spectra (Figure c) display a peak at 531 eV, which is assigned to the transition from O 1s to O 2p/Co 3d . De Groot et al, reported that the peak at 531 eV is related to the metal 3d states, which might be split into two peaks assignable to t 2g and e g .…”
Section: Resultsmentioning
confidence: 95%
“…Although many papers report the magnetic and electronic properties of R 1-x A x MnO 3 1820 , they mostly report on bulks and much less often on films 2124 . For future applications of manganite films, a detailed characterization of the film properties is required.…”
Section: Introductionmentioning
confidence: 99%
“…The pre-edge feature in the O K-edge spectra (around 529.4 eV) is due to the strong hybridization between Mn 3d and O 2p orbitals [43]. This energy position near 530 eV is mainly contributed from the t 2g states [43]. Therefore, the increase of this peak intensity suggests an increasing number of unoccupied Mn 3d t 2g ↓ states coupled with O 2p states.…”
Section: Resultsmentioning
confidence: 95%
“…It can be seen that the intensity of peak A increases with decreasing temperature. The pre-edge feature in the O K-edge spectra (around 529.4 eV) is due to the strong hybridization between Mn 3d and O 2p orbitals [43]. This energy position near 530 eV is mainly contributed from the t 2g states [43].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation